Study of Demographic and Clinical Profile of Injuries Related to "Kite Flying" Celebration in Urban India - Bhavesh Jarwani; Mehul Gajjar; Urjita Modi; Rajvi Patel; Rohan Parekh; Sanket Nandani (Medsci Publications, 2020)
Introduction: Kites were first introduced by the Chinese more than three thousand years ago, but in places like India, Pakistan and Afghanistan, Kite flying is celebrated in unique way. People enjoy cutting down others kites and there is an instinct to catch the threads of the "Cut-Kite" and rejoice the gain. In this study conducted at a tertiary care emergency medicine department to understand demographic profile and injuries related in such a festive celebration, occurring in one urban area, to spread awareness and reduce such incidence. Methodology: This cross-sectional descriptive study was conducted using preformatted form in consecutive two year. Results: Among 83 cases we studied, 81% were male. 65% were in the age group of 11-40. 70% incidences took place in noon and evening hours. 68.67 % presented in 108 ambulance services, 43% presented with fall from height (terraces), 34 % had road traffic accidents because of strings and festival related excitement. Maximum had fall from 1 storey buildings. 56% received Out Patient based treatment. Among the admitted patients 15% had head injury, 2 cut throat, 9.7% had fractures and 1 had to undergo laparotomy, 2 died eventually during the hospital stay because of grievous injuries. Conclusion: This study re-emphasizes the importance of spreading awareness and increasing the care, particularly of children during such an enjoyable festival.